Long-Term Follow-Up following Condylotomy in a Case of Traumatic Unilateral Anterosuperior Mandibular Condyle Dislocation. (14th May 2019) - Nabil, Syed; Kuppusamy, Elavarasi; Nordin, Rifqah; Nazimi, Abdul Jabar; Ramli, Roszalina
Abstract : Anterosuperior temporomandibular joint dislocation is rare. Manual reduction of such dislocation is difficult especially when treatment is delayed. Therefore, it has an increased likelihood of needing surgical intervention to achieve reduction. The authors report a case of an anterosuperior temporomandibular dislocation in a 19-year-old male following a motor vehicle accident. Difficulties were encountered in reducing the dislocation necessitating surgically assisted reduction. The long-term outcome following management by condylotomy is reported. This present report also reviews the literature regarding the classification and management of this uncommon dislocation.